How do adolescents deal with intrusive parenting? The role of coping with psychologically controlling parenting in internalizing and externalizing problems. (October 2020) - Flamant, Nele; Haerens, Leen; Mabbe, Elien; Vansteenkiste, Maarten; Soenens, Bart
Abstract: Introduction: While research has shown convincingly that psychologically controlling parenting increases the risk for internalizing and externalizing problems among adolescents, little is known about how adolescents cope with such parenting. This study examined the role of two non-autonomous ways of coping (i.e., compulsive compliance and oppositional defiance) and one more autonomous way of coping (i.e., negotiation) in the associations between psychologically controlling parenting and internalizing and externalizing problems. Method: Two-wave data from a larger longitudinal study with Belgian adolescents (N = 198; 51% female; mean age = 14.89 years, range = 13–17 years) were analyzed using multilevel modeling. Results: The results showed that oppositional defiance exacerbated associations between psychologically controlling parenting and externalizing problems at the between-person level of analysis. Both compulsive compliance and negotiation exacerbated the association with internalizing problems at the within-person level. In addition to these moderating effects, both oppositional defiance and negotiation played a partly mediating role in associations between psychologically controlling parenting and externalizing problems and oppositional defiance partly mediated associations between psychologically controlling parenting and internalizing problems at the between-person level. Conlusion: Overall, results suggest that oppositional defiance and compulsive compliance are rather dysfunctional coping responses and that negotiation is a mixed blessing. Directions for future research are discussed.